2019
DOI: 10.1038/s41612-019-0081-9
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol mixing state revealed by transmission electron microscopy pertaining to cloud formation and human airway deposition

Abstract: Aerosol mixing state is one of the most important factors determining the impacts of aerosol particles on aerosol-cloud-climate interactions and human health. The size, composition, and morphology of about 32,000 single particles are analyzed using transmission electron microscopy (TEM) to evaluate per-particle mixing state. Based on the TEM analysis, we quantify aerosol mixing state and examine the impacts of per-particle mixing state on cloud condensation nuclei (CCN) properties and particle deposition effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…Our results indicate that external mixing is associated with a high number concentration. Health effects of chemical mixing state are largely unexplored and therefore uncertain, but some studies have revealed a potential health influence of particle mixing state (Ching et al 2019;Ching and Kajino 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that external mixing is associated with a high number concentration. Health effects of chemical mixing state are largely unexplored and therefore uncertain, but some studies have revealed a potential health influence of particle mixing state (Ching et al 2019;Ching and Kajino 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The childcare facilities have led the way in demonstrating many of the links between environmental exposures and health outcomes. Some bioaerosols could also be adsorbed to the inhalable aerosols and transported in environments that have potential pollutant sources [16,30,31]. This study showed that PM concentrations, especially respirable-sized PM, are related to the culturable bioaerosol based on the size-selective concentration.…”
Section: Discussionmentioning
confidence: 73%
“…During indoor and outdoor air quality monitoring, it was confirmed that outdoor harmful pollutants were penetrating indoors [21]. Inhalable aerosols that have penetrated the respiratory tract have different deposition rates [6,16] depending on the location of the respiratory system, and deposition levels and transport patterns provide important clues for assessing the potential health effects of aerosols [15,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations